Evaluation of the Role of PRP in Acute Tibial Shaft Fractures Fixation With IM Nail: A Double-Blinded Randomized Controlled Trial - Wittawat Boonyanuwat; BhupaAk Engkapawastr; Pinkawas Kongmalai (Advances in Orthopedics)
Discussion: PRP significantly enhances midstage fracture healing in tibial shaft fractures, as evidenced by improved callus formation and reduced time to union. These results indicate that PRP holds promise as a therapeutic adjunct for managing tibial fractures. Additional studies with larger sample sizes and diverse fixation techniques are needed to validate these findings and further assess the broader potential of PRP in orthopedic practice.